Evaluation of antiwear activity of substituted benzoylhydrazones and their copper(ii) complexes in paraffin oil as efficient low SAPS additives and their interactions with the metal surface using density functional theory - Jaiswal V.; Gupta S.R.; Rastogi R.B.; Kumar R.; Singh V.P. (My University, 2025)
Sulfur, phosphorus and halogen-free benzoylhydrazones of the formula (HL) [where HL = acetophenonebenzoylhydrazone, H-Abh; and salicylaldehydebenzoylhydrazone, H-Sbh] and their copper(ii) complexes (CuL2) have been synthesized and characterized by FT-IR, NMR spectroscopy and Mass spectrometry. The antiwear performance of these compounds as antiwear additives in paraffin oil has been evaluated using a four-ball tester at an optimized concentration of additives (1% w/v) by varying the load for 30 min test duration and by varying the test durations at 392 N load. Various tribological parameters such as mean wear scar diameter (MWD), mean wear volume (MWV) and wear rates show that ligands and the conventional zinc dibutyldithiophosphate (ZDDP) effectively enhance the antiwear properties of the base lube and possess high load bearing ability. The ligand H-Sbh shows much better antiwear efficiency than H-Abh. Upon complexation the efficiency has increased tremendously in the both cases following the same order as the ligands thereof. The surface topography of the wear track has been studied by Scanning Electron Microscopy (SEM) and Atomic Force Microscopy (AFM) at various test conditions. The AFM and SEM micrographs of wear scar lubricated with copper complexes at different conditions show a drastic decrease in surface roughness in comparison to ZDDP/ligands/paraffin oil alone. The enhanced antiwear behavior of copper complexes is attributed to the in situ formation of a tribofilm under sliding contact which eventually leads to energy saving and prevents material loss. Tribochemistry of the worn surface has been investigated using X-ray photoelectron spectroscopy (XPS) which shows that the protective tribofilm/s is composed of CuO, Cu2O, nitrogen in the form of -NC/-N-C-, adsorbed carbon in the form of -C-C-/-C-H, -C-O- moieties and Fe2O3 and/or Fe3O4. Theoretical calculations based on density functional theory (DFT) for the interactions of different additives with the metal surface strongly match with the observed experimental results. Copper strip corrosion tests show non-corrosive behavior of the additives. These additives also show non-corrosive behavior towards AISI 52100 steel in paraffin oil. © 2015 The Royal Society of Chemistry.